Adsorption of 2, 4-dichlorophenoxyacetic acid in an aqueous medium on nanoscale MIL-53(Al) type materials. Issue 40 (27th September 2019) - Isaeva, Vera I.; Vedenyapina, Marina D.; Kulaishin, Stanislav A.; Lobova, Anna A.; Chernyshev, Vladimir V.; Kapustin, Gennady I.; Tkachenko, Olga P.; Vergun, Vadim V.; Arkhipov, Danil A.; Nissenbaum, Vera D.; Kustov, Leonid M.
Abstract : MIL-53(Al) type materials were prepared using MW-activation. They show high adsorption capacities in the adsorption of 2, 4-dichlorophenoxyacetic acid in an aqueous medium and demonstrate faster adsorption rates as compared to an activated carbon. Abstract : A series of flexible metal–organic frameworks (MOFs) belonging to the MIL-53 family, such as MIL-53(Al), its amino-functionalized analog NH2 -MIL-53(Al), and MIL-53(Al) type materials with Al 3+ ions and mixed benzene-1, 4-dicarboxylate and 2-aminobenzene-1, 4-dicarboxylate linkers (MixLR ) in various proportions were prepared in a nanocrystalline form using MW-activation under atmospheric pressure according to the original solvothermal procedure. The MIL-53(Al) and NH2 -MIL-53(Al) samples feature nanocrystals with sizes of 200–300 nm, while MixLR matrices synthesized in this manner are composed of small nanoparticles with sizes of about 20–30 nm. MIL-53(Al) type materials (MIL-53(Al), NH2 -MIL-53(Al) and MixLR ) were probed in the adsorption of a typical herbicide 2, 4-dichlorophenoxyacetic acid (2, 4-D) in an aqueous medium. This study revealed a strong impact of the flexibility and porosity of the synthesized MIL-53(Al) type matrices on their physicochemical characteristics. MIL-53(Al) type materials show much higher 2, 4-D adsorption rates than an activated carbon matrix (CSAC). The structural characteristics of the studied MIL-53(Al) type materials were established with a high resolution X-ray powder diffractometer equipped with a synchrotron radiation source. The obtained results can be used for the development of advanced adsorbents based on MIL-53(Al) type materials for water remediation.